VIII Ganz schön weise - Bergmann, Claudia Dorit (Gottesdienste mit Kindern 2019)

IX Echt stark! - Bergmann, Claudia Dorit (Gottesdienste mit Kindern 2020)

Exact Constraint Satisfaction for Truly Seamless Parametrization - Mandad, Manish; Campen, Marcel (Computer Graphics Forum)
Abstract In the field of global surface parametrization a recent focus has been on so‐called seamless parametrization. This term refers to parametrization approaches which, while using an atlas of charts to enable the handling of surfaces of arbitrary topology, relate the parametrization across the cuts between charts via transition functions from special classes of transformations. This effectively makes the cuts invisible to applications which are invariant to these specific transformations in some sense. In actual implementations of these parametrization approaches, however, these restrictions are obeyed only approximately; errors stem from the tolerances of numerical solvers employed and, ultimately, from the limited accuracy of floating point arithmetic. In practice, robustness issues arise from these flaws in the seamlessness of a parametrization, no matter how small. We present a robust global algorithm that turns a given approximately seamless parametrization into an exactly seamless one ‐ that still is representable by standard floating point numbers. It supports common practically relevant additional constraints regarding boundary and feature curve alignment or isocurve connectivity, and ensures that these are likewise fulfilled exactly. This allows subsequent algorithms to operate robustly on the resulting truly seamless parametrization. We believe that the core of our method will furthermore be of benefit in a broader range of applications involving linearly constrained numerical optimization.

Distortion-minimizing injective maps between surfaces - Schmidt, Patrick; Born, Janis; Campen, Marcel; Kobbelt, Leif (ACM Transactions on Graphics)
The problem of discrete surface parametrization, i.e. mapping a mesh to a planar domain, has been investigated extensively. We address the more general problem of mapping between surfaces. In particular, we provide a formulation that yields a map between two disk-topology meshes, which is continuous and injective by construction and which locally minimizes intrinsic distortion. A common approach is to express such a map as the composition of two maps via a simple intermediate domain such as the plane, and to independently optimize the individual maps. However, even if both individual maps are of minimal distortion, there is potentially high distortion in the composed map. In contrast to many previous works, we minimize distortion in an end-to-end manner, directly optimizing the quality of the composed map. This setting poses additional challenges due to the discrete nature of both the source and the target domain. We propose a formulation that, despite the combinatorial aspects of the problem, allows for a purely continuous optimization. Further, our approach addresses the non-smooth nature of discrete distortion measures in this context which hinders straightforward application of off-the-shelf optimization techniques. We demonstrate that, despite the challenges inherent to the more involved setting, discrete surface-to-surface maps can be optimized effectively.

Parametrization quantization with free boundaries for trimmed quad meshing - Lyon, Max; Campen, Marcel; Bommes, David; Kobbelt, Leif (ACM Transactions on Graphics)
The generation of quad meshes based on surface parametrization techniques has proven to be a versatile approach. These techniques quantize an initial seamless parametrization so as to obtain an integer grid map implying a pure quad mesh. State-of-the-art methods following this approach have to assume that the surface to be meshed either has no boundary, or has a boundary which the resulting mesh is supposed to be aligned to. In a variety of applications this is not desirable and non-boundary-aligned meshes or grid-parametrizations are preferred. We thus present a technique to robustly generate integer grid maps which are either boundary-aligned, non-boundary-aligned, or partially boundary-aligned, just as required by different applications. We thereby generalize previous work to this broader setting. This enables the reliable generation of trimmed quad meshes with partial elements along the boundary, preferable in various scenarios, from tiled texturing over design and modeling to fabrication and architecture, due to fewer constraints and hence higher overall mesh quality and other benefits in terms of aesthetics and flexibility.

Seamless Parametrization with Arbitrary Cones for Arbitrary Genus - Campen, Marcel; Shen, Hanxiao; Zhou, Jiaran; Zorin, Denis (ACM Transactions on Graphics)
Seamless global parametrization of surfaces is a key operation in geometry processing, e.g., for high-quality quad mesh generation. A common approach is to prescribe the parametric domain structure, in particular, the locations of parametrization singularities (cones), and solve a non-convex optimization problem minimizing a distortion measure, with local injectivity imposed through either constraints or barrier terms. In both cases, an initial valid parametrization is essential to serve as a feasible starting point for obtaining an optimized solution. While convexified versions of the constraints eliminate this initialization requirement, they narrow the range of solutions, causing some problem instances that actually do have a solution to become infeasible. We demonstrate that for arbitrary given sets of topologically admissible parametric cones with prescribed curvature, a global seamless parametrization always exists (with the exception of one well-known case). Importantly, our proof is constructive and directly leads to a general algorithm for computing such parametrizations. Most distinctively, this algorithm is bootstrapped with a convex optimization problem (solving for a conformal map), in tandem with a simple linear equation system (determining a seamless modification of this map). This initial map can then serve as a valid starting point and be optimized for low distortion using existing injectivity preserving methods.

Intergenerationelle Beziehungen in der Familie - Buhl, Heike M.; Sommer, Sabrina (Psychotherapie im Alter)
Beziehungen zwischen Erwachsenen und ihren Eltern sind durch Interdependenzen und Dependenzen gekennzeichnet. Während das Zusammenleben von Familien mit Kindern im mittleren Erwachsenenalter dabei ganz überwiegend durch Interdependenz geprägt ist, nehmen im Alter Dependenzen durch gesundheitliche Beeinträchtigungen der Eltern zu. Mit Blick darauf werden im Artikel behaviorale, kognitive und emotionale Merkmale von Eltern-Kind-Beziehungen erläutert und theoretisch in zentrale Konzepte eingebettet. Das Verhalten ist durch Solidarität zwischen den Generationen, aber auch durch Aspekte des Einflusses innerhalb der Beziehung und aufeinander, gekennzeichnet. Um Familienkognitionen zu beschreiben, werden die verwandten Konzepte der Individuation und der filialen Reife herangezogen. Verhalten, wie auch Kognitionen, sind eng mit dem dritten Beziehungsmerkmal, der Affektivität verknüpft, das neben positiven auch negative Gefühle sowie Ambivalenzen umfasst.

Feedback in internet-based self-assessments and its effects on acceptance and motivation - Bohndick, Carla; Menne, Christina; Kohlmeyer, Susanne; Buhl, Heike M. (Journal of Further and Higher Education)
Internet-based self-assessments (ISAs) are tools used to support finding the right educational fit for higher education (HE) students. ISAs typically consist of a questionnaire followed by a feedback report about the results. It is unknown how the characteristics of the feedback report itself affect individuals’ acceptance and motivation to follow the advice from the report. Literature on feedback in general has suggested relationships between acceptance of feedback and motivation, feedback sign (positive versus negative) and regulatory focus (promotion focus versus prevention focus), influence acceptance and the motivation to develop. To investigate if these findings are transferable to the context of ISAs, we conducted an online study with N = 249 German university students (73% female; M = 22.84 years of age (SD = 3.73)) and a bogus self-assessment. Feedback sign was manipulated randomly, and the regulatory focus was measured by values. Regression analyses indicate a positive effect of positive feedback sign, but no differences regarding regulatory focus.

Anstoß und Unterstützung der professionellen Weiterentwicklung im Lehramtstudium durch weiterentwicklungsorientiertes Online-Self-Assessment - Bohndick, Carla; Kohlmeyer, Susanne; Buhl, Heike M. (Lehrerbildung auf dem Prüfstand)

Bedingungen elterlichen Unterstützungsverhaltens beim Lesen im Grundschulalter. Eine Untersuchung relevanter Prozessmerkmale - Hilkenmeier, Johanna; Wiescholek, Sabrina; Buhl, Heike M. (Zeitschrift für Soziologie der Erziehung und Sozialisation)

Fit für Inklusion - Entwicklung und Validierung einer deutschsprachigen Kurzskala zum Umgang mit Heterogenität - Kohlmeyer, Susanne; Buhl, Heike M.; Bonanati, Sabrina; Dannowsky, Janika; Bohndick, Carla (Empirische Pädagogik)

Autobiographik als ritterschaftliche Selbstverständigung. Ulrich von Hutten, Götz von Berlichingen, Sigmund von Herberstein - Moritz, Tilman

Das Elterngespräch aus Forschungsperspektive. Strategien zur Förderung elterlichen Engagements - Hilkenmeier, Johanna; Greiner, Christian; Buhl, Heike M. (SCHULE inklusiv)

Wertschätzung und Förderung - Mehrsprachigkeitsorientierung im Fremdsprachenunterricht - Göbel, Kerstin; Schmelter, Lars; Frankemölle, Bernd; Frede, Georgia; Buret, Julie (Lernende Schule)

Rezension zu: „Der immer neue Exodus” - Bergmann, Claudia Dorit (Review of Biblical Literature)

Unheard music – Notes on silent music moments. - Ahrens, Stephan

LEXIKON. Eintrag (Einzelartikel) - Ptashnyk, Stefaniya (WSK Grammatik (online-Publikation))

His Bloody Deceptive Project: The Unjustified Confessions of Roderick Macrae - Wirth, Robert (Le Crime, Le Chatiment et Les Écossais /Crime, Punishment and the Scots)

Complicity and the Politics of Representation

Scotland: A Nation-State in Waiting - Wirth, Robert (Timescapes of Waiting: Spaces of Stasis, Delay and Deferral)